Agronomic evaluation of peanut genotypes in the western region of the state of São Paulo - Bazanella, Marcel Rodrigo (2021)
ABSTRACT This work aimed at the agronomic evaluation of peanut genotypes in the western region of the state of São Paulo. The experiment was conducted in the commercial production area of "‹"‹Amenco Peanuts, located in the city of Getulina-SP, in the western region of the state of São Paulo, in the agricultural year 2020/21. It was implemented on December 17, 2020, outside the ideal sowing period, together so that it was possible to evaluate the productive potential and the agronomic characteristics of the genotypes under extreme conditions. The experimental design used was in randomized blocks, with four replications. The treatments were thirteen peanut genotypes, eleven lines (2091 OL, 2133 OL, 1253 OL, 2131 OL, 2110 OL, 2136 OL, 2010 OL, 2101 OL, 2056 OL, 1876 OL and 2250 OL), one cultivar (BRS 423 OL), all developed by Embrapa's Peanut Improvement Program and an Argentine cultivar by El Carmen (Granoleico). The plots consisted of two lines of three meters in length, with a spacing of 0.90 m and plot area of "‹"‹5.4 m2. Black spot severity, 100 grain mass and pod yield were evaluated. Based on the present field study, it is concluded that the lowest severity scores were obtained with the BRS 423 OL and 2091 OL genotypes. The largest masses of 100 grains were found with 2010 OL and 1253 OL. Finally, the highest yields were obtained with 2010 OL, 2110 OL, 2101 OL, BRS 423 OL, 2136 OL, 1253 OL and 2133 OL.